Physicochemical Properties and Microbial Load of Cow Milk Collected from Milk Supply Chain during Winter and Summer in Khartoum State, Sudan - Warsama, L. M.; Mustafa, N. E. M.; El Zubeir, I.E.M. (Journal of Veterinary Medicine and Animal Production, 2021)
Milk is considered an important chain for transmission of pathogenic microorganisms to human beings unless it is produced and handled under good hygienic conditions. Thus, hygienic production of milk has to get due attention in order to provide high quality milk to the consumers. This study was conducted to evaluate the quality of milk available to the consumers in Khartoum State during winter and summer seasons. Two hundred samples of raw cow’s milk were collected and evaluated for the physicochemical properties of milk (solids not fat; SNF, fat, protein, lactose, acidity and density). In addition the bacteriological examinations (total bacterial, coliform and psychrotrophic bacterial) counts were carried out. The results showed significantly (P≤0.001) higher fat (5.03%) and SNF (11.52%) content of cows’ milk samples obtained during winter. However, highly significant (P≤0.001) values were found in the milk samples collected during summer for content of lactose (4.72%) and acidity (0.19%). Highly significant (P≤0.001) counts for total bacteria (TBC), coliform and psychrotrophic bacteria were obtained for cow’s milk samples collected during summer (log10 7.58, log10 5.54 and log10 2.30, respectively). Hence the study suggested that more efforts are needed to improve milk hygiene and quality by regular monitoring and raising awareness among dairy owners in addition to initiation of milk collection centers coupled with cooling facilities